Efektivitas Program Sosialisasi Pencegahan Stunting Berbasis Edukasi Gizi Terhadap Peningkatan Pengetahuan dan Perilaku Masyarakat di Jorong Labuatan, Nagari Sungai Jambu, Kecamatan Pariangan, Kabupaten Tanah Datar, Sumatera Barat - Zhiverland Irsal; Fitri Juliandini; Hafidza Aulia Putri Anshor; Sherly Fernanda; Salsabila (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2026)
This study aims to analyze the effectiveness of nutrition education-based stunting prevention socialization programs in improving community knowledge and behavior in Jorong Labuatan, Nagari Sungai Jambu, Pariangan District, Tanah Datar Regency, West Sumatra. The background of this study is based on the high prevalence of stunting caused by low public awareness regarding balanced nutrition and child care practices. This research uses a descriptive qualitative method with data collected through in-depth interviews, observation, and documentation. The results indicate that nutrition-based socialization programs improve community understanding of nutritional intake, child feeding practices, and healthy living behaviors. Behavioral changes were also identified in feeding practices and child health awareness. The study concludes that the program is effective in improving knowledge and behavior, although continuous assistance is still required.